Palivizumab Prophylaxis among Infants at Increased Risk of Hospitalization due to Respiratory Syncytial Virus Infection in UAE: A Hospital-Based Study - M. Elhalik; K. El-Atawi; S.K. Dash; A. Faquih; A.D. Satyan; N. Gourshettiwar; A. Khan; S. Varughese; A. Ramesh; E. Khamis (Canadian Respiratory Journal)
Background. Respiratory syncytial virus (RSV) represents a significant public health burden and the leading cause of lower respiratory tract infections globally, and it is the major cause of hospitalization during the winter. We aimed to evaluate the effectiveness of palivizumab prophylaxis to reduce the hospitalization in children at high risk of RSV infection. Methods. We performed a retrospective observational single-arm hospital-based study including five RSV seasons (September to March) from 2012 to 2017. We retrospectively included premature infants born at less than 35 weeks of gestation with chronic lungs disease or hemodynamic significant congenital heart disease for palivizumab prophylaxis against RSV infection according to the criteria presented. Results. A total of 925 children were enrolled in the study over the five RSV seasons. Of them, 410 (44.3%) infants born at <32 weeks of gestation and 515 (55.6%) infants born at 32–35 weeks of gestation with mean (±SD) birth weight of 1104.8 ± 402.85 and 1842.5 ± 377.5, respectively. The compliance with the course of palivizumab was reported in 841 (90.9%) children. Of them, about 75 (8.9%) hospitalized children were reported, and 17 (2.02%) RSV positive children were detected. Hospitalization due to RSV infection was decreased from 9.23% in the 2012-2013 season to 0.67% in the 2016-2017 season. Conclusion. This study demonstrated that palivizumab prophylaxis in children at high risk of developing RSV infection was effective in reducing the risk of hospitalization with a high compliance rate over the five RSV seasons.